Impact of Irrigation Water Technification on Seven Directories of the San Juan-Patoa River Using Plithogenic n-SuperHyperGraphs Based on Environmental Indicators in the Canton of Pujilí, 2021 - Yenson Vinicio Mogro Cepeda; Marco Antonio Riofrío Guevara; Emerson Javier Jácome Mogro; Rachele Piovanelli Tizano (Neutrosophic Sets and Systems)
The study analyzed interactions among economic, environmental, and sociocultural factors in agricultural irrigation systems to evaluate and promote integral sustainability, using the application of plithogenic n-SuperHyperGraphs. Significant interactions between vertex attributes were identified dur ing the study's development. Results highlighted that optimizing economic profitability, implementing ecological pest management, and fostering social cohesion are essential for improving system sustaina bility. It is concluded that an interdisciplinary approach is critical for achieving comprehensive agricul tural sustainability, proposing an evaluative model adaptable to local settings to strengthen sector resil ience. Additionally, the application of plithogenic n-SuperHyperGraphs provides a useful tool across various study areas for management and decision-making in diverse agricultural environments.